The effect of perceived relative deprivation in leader-member exchange on flow experience: the serial mediating role of perceived relative deprivation in coworker exchange and job-related anxiety - Seçkin, Şeyda Nur; Çağlın, Cahit (Frontiers in Psychology, 2026)
IntroductionFlow, first conceptualized by Csikszentmihalyi, refers to a state of deep engagement and intrinsic enjoyment in an activity. Within organizational settings, flow at work has been associated with enhanced productivity, creativity, motivation, and job satisfaction. However, while previous studies have focused primarily on the factors that facilitate flow, research examining interpersonal or relational barriers remains scarce. Drawing on Relative Deprivation Theory, this study explores whether perceived relative deprivation in leader-member interactions hinders the experience of flow at work and whether perceived relative deprivation in coworker interactions and job-related anxiety mediate this relationship among nurses-a profession characterized by high task demands and strong interdependence.MethodsA cross-sectional survey design was employed, with data collected from 406 nurses. Validated instruments measured perceived relative deprivation in leader-member and coworker interactions, job-related anxiety, and flow at work. Mediation analyses were conducted to examine direct and indirect pathways between the variables.ResultsPerceived relative deprivation in leader-member interactions did not have a direct effect on flow at work. However, higher perceived relative deprivation in leader-member interactions predicted greater perceived relative deprivation in coworker interactions, which subsequently increased job-related anxiety and reduced flow at work.DiscussionThe findings suggest that relational deprivation in the workplace indirectly diminishes flow by elevating job-related anxiety. These results underscore the importance of fostering equitable and supportive leader-member relationships and cohesive coworker dynamics to promote optimal psychological engagement and well-being among nurses.